The critical x[I/L]xbS motif in adaptor proteins, MAVS, MITA, and TRIF contributes to type I IFN production and antiviral immune response in fish - Xue Yun Peng; Jing Hou; Bo Li; Chuan Yun Zhang; Lin Huang; Lan Hao Liu; Nan Li; Pin Nie; Shan Nan Chen (Fish & Shellfish Immunology, 2026)

Classification of hemocyte subpopulations in the clam Meretrix Petechialis and their differential immune-associated responses to Vibrio infection - Jing Tian; Hongxia Wang; Pin Huan; Baozhong Liu (Fish & Shellfish Immunology, 2026)

Polyvinyl chloride microplastics disrupt spatial purification gradients and amplify antibiotic resistance risks in sulfamethoxazole-stressed constructed wetlands - Yu Xiao; Yangqi Liu; Xi Zhang; Jinping Cheng; Pin Gao (Chemical Engineering Journal, 2026)

Multiscale drivers of arthropod functional guilds in rice agroecosystems: Evaluating the roles of climatic, landscape, and management factors - Yu-Pin Lin; Pei-Chen Lin; Shafira Wuryandani; Chun-Chia Liu; Chiao-Ming Lin; Chi-Wei Tsai; Chi-Lun Huang; Chuan-Kai Ho; Gerard H. Ros (Agriculture, Ecosystems & Environment, 2026)

Regulating interface charge separation to unlock photocatalytic non-radical pathways: Construction of BiOCl/COF S-scheme heterojunction for efficient antibiotic remediation - Hailan Qin; Siyuan Di; Min Liu; Qiuyue Zhang; Pin Chen; Zihan Li; Shukui Zhu (Journal of Cleaner Production, 2026)

Myeloid-derived suppressor cells-guided mesoporous silica nanoplatform delivering a BET inhibitor exerts anticancer effects by reprogramming the immunosuppressive tumor microenvironment - Li-Chan Chang; Li Xu; Yin-Fen Liu; Chang-An Lin; Si-Han Wu; Wen-Pin Su (Chemical Engineering Journal, 2026)

Funnel-bottom smart pond engineering reduces dissolved inorganic nitrogen accumulation in intensive shrimp culture - Hsueh-Han Hsieh; W. Sanjaya Weerakkody; Pin-Chun Liu; Ing-Jer Huang; Chin-Chang Hung (Aquacultural Engineering, 2026)

Protected areas on international borders show uneven conservation outcomes - Rachakonda Sreekar; Hoong Chen Teo; Tiantian Zhang; Jiajia Liu; Aakash Lamba; Jun Ying Lim; Lian Pin Koh; Sean Jing Wen Ng; Janice Ser Huay Lee; James E. M. Watson; Yiwen Zeng (Conservation Biology, 2026)
Border protected areas (BPAs) are national protected areas that are immediately adjacent to a country's border or span two or more countries; they are characterized by distinctive opportunities and pressures. They play a critical role in protecting carbon‐rich ecosystems, conserving endangered biodiversity, reducing cross‐border environmental threats, and promoting peace and cooperation. At the same time, compared with other protected areas within the same country, BPAs may be particularly vulnerable to asymmetric enforcement, cross‐border leakage, conflict, and weak institutional coordination. Using a pixel‐level propensity score matching approach, we conducted the first global assessment of forest loss in BPAs relative to counterfactuals in nonborder protected areas within the same country. We found that compared with nonborder protected areas, most BPAs (81%) experienced lower or similar forest loss rates, preventing the loss of 112,036 ha of forest and ∼3.69 MtCO 2 e/year in emissions between 2013 and 2022. However, the remaining 19% of BPAs experienced significantly higher forest loss than their counterfactuals, resulting in the loss of 87,657 ha and additional emissions of ∼2.85 MtCO 2 e/year. Importantly, BPA underperformance was not driven solely by lower border protection feasibility as larger reserve size and closer proximity to urban centers were also associated with higher forest loss. Drivers of forest loss in underperforming BPAs varied regionally: agriculture expansion dominated in Africa and Asia; regulatory mismatches in timber regulations were most important in Europe; and wildfire risk was a key factor in North America. We further identified mainland Southeast Asia and the Congo Basin as urgent border conservation hotspots, where high deforestation pressure threatens both endangered species and carbon‐rich forests. Thus, BPA underperformance is geographically concentrated and not pervasive. Targeted regional interventions would enhance cross‐border cooperation, mobilize sustainable financing, and strengthen governance structures, while also facilitating the effective integration of BPAs into global biodiversity and climate policy frameworks.

A comparative study of methods for quantifying sand-sized sediment grain textural parameters - Xiaotian Shen; Xing Jian; Wei Zhang; Ruolan Liao; Dongming Hong; Chao Li; Shaohua Zhao; James T. Liu; Yuan-Pin Chang (Sedimentary Geology, 2026)

Effects of dietary rumen-protected bile acids on muscle fiber composition and drip loss in Hu sheep (Ovis aries): insights from transcriptomic and metabolomic analyses - Zhe Wang; Manman Hou; Dan Hu; Jie Huang; Qi Liu; Pin Song; Yue Chen; Pengnan Chen; Yuyang Yin; Aizhi Cao; Yufeng Li; Yingdong Ni (Food Bioscience, 2026)

Poly(lactic-co-glycolic acid) (PLGA)-based vaccine delivery systems for fish: physicochemical properties, immunological mechanisms, and applications - Shu-Chun Chuang; Yi-Chen Lin; Ya-Shuan Chou; Shang-Pin Liu; Shao-Wen Hung; Ti-Chun Chang; Chung-Hwan Chen; Chung-Da Yang (Fish & Shellfish Immunology, 2026)

Cyprinid herpesvirus 2 (CyHV-2) ORF53 inhibits NF-κB signalling by targeting p65 degradation - Chuan Yun Zhang; Zheng Liu; An Ning Pang; Jia Yi Li; Bo Li; Nan Li; Lan Hao Liu; Pin Nie; Shan Nan Chen (Fish & Shellfish Immunology, 2026)

Role of Mesoscale Eddies in Modulating Sea Surface Temperature off the Southeast Atlantic Coast Based on a Regional Ocean Model - Pin Li; Shidong Liu (Journal of Ocean University of China, 2026)

Mapping climate-conditioned PM2.5 response under climate change in Taiwan using a high-resolution Geo-AI model - Pei-Yi Wong; Wei-Lun Hsu; Chieh-Ying Chen; Chien-Fei Chen; Chia-Wei Hsu; Shih-Chun Candice Lung; Ta-Chih Hsiao; Chia-Pin Yu; Wan-Yu Liu; Pau-Chung Chen; Wei Jie Seow; Chien-Hao Sung; et al. (Journal of Environmental Management, 2026)

Type I IFNs, IFNc, IFNd1, IFNd2, IFNh, and type II IFNs, IFN-γ and IFN-γrel, and their possible receptors with the identification of two variants of IFNc and IFNh in turbot (Scophthalmus maximus) - Bo Li; Meng Xin Yan; Yu Hang Deng; Xiao Qian Jiao; Shan Nan Chen; Xu Jia Zhang; Jia Le Chen; Xue Yun Peng; Lan Hao Liu; Pin Nie (Fish & Shellfish Immunology, 2026)

The dynamics of microbial communities in the host, water and sediment during the metamorphosis of Ruditapes philippinarum larvae - Yong Huang; Hongxia Wang; Jun Fang; Pin Huan; Baozhong Liu (Aquaculture, 2026)

Diffusion of iodide in compacted Beishan Granite: Impact of saturation duration, ionic strength, and dry density - Yunpeng Yi; Jiayu Zhou; Hengtao Liu; Wujian Jin; Jingye She; Danwen Qin; Chuan-Pin Lee; Hanyu Wu; Mingliang Kang (Journal of Environmental Radioactivity, 2026)

Genome-wide identification, expression analysis and antiviral function of RIG-I-like receptors (RLRs) in basal chordate Branchiostoma japonicum - Yueying Du; Yuhang Deng; Ruixue Liu; Jialing Yuan; Yunxia Wang; Su Wang; Pin Nie; Xiaojun Song (Fish & Shellfish Immunology, 2026)

Aging attenuates threat: how moderate aging of microplastics suppresses antibiotic resistance gene proliferation during sludge anaerobic digestion - Jinling He; Ai Zhang; Lin Wang; Qian Ping; Pin Gao; Yanan Liu (Bioresource Technology, 2026)

WS2-modified schwertmannite for highly efficient dye wastewater degradation via enhanced Fe cycle in heterogeneous Fenton-like catalysis - Kun Feng; Shuping Zhang; Neng Tao; Zhiyi Sun; Xianqiang Kong; Yuanyu Tan; Xuhao Liu; Lixiang Zhou; Pin Zhou; Yongjun Shen; Ting Li (Journal of Environmental Sciences, 2026)

Design Rules for Robust Coronary Artery Segmentation: A Systematic Analysis of Dataset Size, Windowing, Architectures, and Vessel Geometry - Ming-Hui Hung; Yu-Wei Chiang; Hao-Yun Liu; Han-Hsuan Chu; Yu-Sen Huang; Pin-Yi Chiang; Hsin-Ming Chen; Tzung-Dau Wang; Shyh-Jye Chen; Wen-Jeng Lee (Annals of Biomedical Engineering, 2026)

SAR-to-EO image translation with multi-kernel-size convolutions - Jingqin Mu; Yuzhu Wang; Sheng Zhan; Guoqing Yao; Jiarui Tian; Pin Liu (International Journal of Remote Sensing, 2026)

Formation and cytotoxicity of drinking water disinfection byproducts in oxidation processes followed by chlorine and chloramine disinfection - Pin Hou; Ziqi Li; Feiyu Zhai; Yunsi Liu; Chao Liu (Journal of Environmental Chemical Engineering, 2026)

Lipid accumulation by triphenylphosphine oxide with simultaneous neural dysregulation and microbiota changes - Youjia Liu; Yangyuan Zhou; Pin Gao; Zhenyang Yu; Daqiang Yin (Journal of Environmental Sciences, 2026)

Sea buckthorn for future foods: bioactive mechanisms, synthetic biology, and precision delivery systems - Nan Li; Peidong Fan; Lulu Wang; Luole Feng; Hui Long; Wenjuan Yang; Jing Wang; Yanni Zhao; Huan Liu; Yuxi Guo; Pin Gong (Food Research International, 2026)

Immunomodulatory mechanism of Pleurotus eryngii polysaccharides in acrylamide-induced mice via the P2X7-NLRP3 pathway, metabolic homeostasis and gut microbiota - Jing Wang; Xiuxiu Liu; Dongliang Jin; Man Wang; Nan Zhang; Yanni Zhao; Wenjuan Yang; Nan Li; Xuefeng Chen; Pin Gong (Food Bioscience, 2026)

Social behavior of masked palm civet in an urban habitat - Po-Jun Chuang; Pin Xuan Lim; Shan-Min Chen; Pin-Huan Yu; Wei-Ting Liu; Hui-Yun Tseng (Mammal Research, 2026)

Development of an artificial intelligence (AI) marine scientific research model: The case of marine science and technology policy and its legitimate practice in Taiwan - Juei-Cheng Jao; Chiao-Wen Lin; Pin-Chien Chen; Yi-Cheng Chang; Yi-Juen Chen; Wen-Hong Liu (Marine Policy, 2026)

Widely targeted metabolomics reveals chemical mechanism of bloating in Rosa roxburghii Tratt juice induced by vitamin C and its chiral isomers - Hong Yang; Yuting Liu; Xinying Wang; Wenxin Zhang; Bo Peng; Dalong Chen; Angze Gao; Weixin Huang; Pin Qian; Deshun Yu; Yifu Tian; Xianzhi Dong (Food Chemistry, 2026)

Infrared thermal imaging as a non-invasive predictive tool for early detection of flap necrosis after breast cancer surgery: A prospective cohort study - Jiangnan Yao; Pin Fang; Haiyan Zhang; Ping Liu; Xiaoqiong Jiang; Pan Huang; Fuman Cai (Journal of Thermal Biology, 2026)

Pyrolysis behaviors of lump sub-bituminous coal. Part 2: Effect of particle size - Zong-Pin Fu; Le-Le Qiu; Yi-Bin Huang; Yun-Peng Zhao; Jian Zhou; Jing Liang; Jian Xiao; Fang-Jing Liu (Fuel, 2026)

Optimization of gradient anisotropic voronoi porous structures based on machine learning - Wei Cao; Hanxuan Lin; Bin Liu; Pin Lu; Wenhui Shen; Jinwang Huang (Engineering Structures, 2026)

Coupled oxygen and nitrogen defect sites in Co-N4-coordinated frameworks facilitate stepwise CO2 methanation - Pin-Yu Liu; Sheng-Xiang Chou; Wei-Tse Sun; Hsin-Han Chen; Cheng-Hung Tsai; Yen-Lin Lai; Yu-Cheng Shao; Chi-Liang Chen; Yu-Ching Huang; Yun-Wei Chiang; Bo-Hong Liu; Chia-Hsin Wang; et al. (Chemical Engineering Journal, 2026)

Biomimetic microneedle patch integrating ROS-scavenging nanoceria, anti-inflammatory phytochemical, and macrophage-membrane-coated nanoparticles for local hepatic therapy of endotoxemia - Bingwen Zhu; Chang Sun; Dongrong Luo; Zhongliang Zhang; Linguo Cao; Tao Bi; Aolin Jiang; Yuying Liang; Zehui Jiang; Haihua Luo; Pin Jiang; Shaoqing Liu; et al. (Chemical Engineering Journal, 2026)

Closed-loop recycling and recovery of vanadium cathodes from waste aqueous zinc-ion batteries - Hsing-Kai Tseng; Jun-An Su; I-Mao Chen; Yu-Ze Chen; Jun-Yi Wu; Pin-Han Chen; Fan-Wei Liu (Chemical Engineering Journal, 2026)

Experimental investigation and characterization of the vibration fatigue S-N curve for small-diameter 316L stainless steel butt-welded pipes - Ning Li; Hongbo Gao; Lei Lin; Pin Li; Shuai Zhou; Han Liu; Changning Li; Decheng Xu; Yin Liu; Zhilin Chen (Annals of Nuclear Energy, 2026)

A novel single-cell communication framework combining multi-omics reveals neuro-viral pathogenesis in fish - Yi-Fan Liu; Teng-Fei He; Zhi-Wen Zhao; Bao-Sheng Wu; Ying Liang; Lin-Miao Li; Jin-Ping Chen; Ye-Pin Yu (Marine Life Science & Technology, 2026)

MHC II system of mandarin fish (Siniperca chuatsi): Gene identification, expression analysis and transcriptional regulation - Jing Hou; Lu Qi; Ran Cao; Lan Hao Liu; Shan Nan Chen; Pin Nie (Aquaculture, 2026)

Beyond simple inhibition: Unveiling the non-monotonic impact and multi-level mechanisms of aged microplastics on sludge anaerobic digestion - Jinling He; Kexin Li; Xianbao Xu; Yongquan Zhou; Ai Zhang; Pin Gao; Xiang Li; Gang Xue; Yanan Liu (Water Research, 2026)

Characterization of monoclonal antibody against IgM and phagocytic function of IgM+ B cells in snakehead (Channa argus) - Peng Fei Mu; Zhe Wang; Qi Li; Qiu Hua Li; Lan Hao Liu; Pin Nie (Fish & Shellfish Immunology, 2026)

Genomic, transcriptional and proteomic clarification of fathead minnow and common carp composition in epithelioma papulosum cyprini (EPC) cell line - Bo Li; Jing Hao Yuan; Yu Hang Deng; Shan Nan Chen; Meng Yao Ji; Xu Jia Zhang; Yang Liu; Zhen Gan; Pin Nie; Lan Hao Liu (Fish & Shellfish Immunology, 2026)

Industrial relocation: its heterogeneous effects on photovoltaic development in China - Pin Li; Jinsuo Zhang; Shaohui Zou; Jing Xiong; Hong Liu; Lei Zhou (Energy Policy, 2026)

Deciphering dose-dependent effects of polypropylene and polyethylene microplastics on digestion performance dynamics and antibiotic resistance development in sludge anaerobic digesters - Yu Xiao; Yangqi Liu; Juan Zhou; Xiaoying Jiang; Pin Gao (Chemical Engineering Journal, 2026)

One-pot remediation of binary organic-metal pollution: Efficient co-removal of BPA and Sb(III) by PMS-activated Fe-Mn@NC catalyst - Shuoshuo Mao; Jingjing Liu; Shanqi Liang; Lei Li; Pin Gao; Fang Li; Juan Zhou (Journal of Environmental Chemical Engineering, 2025)

Dramatically suppressed climate signals in the Yellow River - Yonggui Yu; Rick J. Yang; Gang Wang; Jaap H. Nienhuis; Xianyao Chen; James T. Liu; Marcel van der Perk; Rens van Beek; Xuefa Shi; Shuqing Qiao; Zhi Li; Jay Lee; et al. (Global and Planetary Change, 2025)

Linking source-to-sink processes, organic matter composition, and oxygen consumption on a shallow passive margin shelf sustained by small mountainous rivers - Yu-Shih Lin; Chih-Lin Wei; Yuan-Pin Chang; Jih-Terng Wang; Shu-Ying Chuang; Liang-Chi Wang; James T. Liu; Hong-Chun Li; Chieh-Wei Hsu (Geochimica et Cosmochimica Acta, 2025)

Complement factor D of Paralichthys olivaceus in serum enhances C3 deposition to activate complement against bacterial infection - Heng Liu; Xiao-yan Jin; Xue-pin Han; Yin Liu; Feng Zhang; Mo-fei Li (Fish & Shellfish Immunology, 2025)

A point-of-care testing biosensing platform integrated with physiologically based pharmacokinetic model for on-site therapeutic drug monitoring of methotrexate - Feng-Feng Zhang; Mei-Juan Wu; Zi-Wei Yu; Yi-Lan Lin; Pin-Fang Huang; Meng-Meng Liu (Chemical Engineering Journal, 2025)

Salinity-dependent responses differentiate branchial ion regulation during acute hypothermal stress in euryhaline Indian Medaka - Naveen Ranasinghe; Salman Akram; Shi-Shien Lee; Pin-Jhu Liao; Tsung-Jui Yang; Yu-Chieh Kung; Tsung-Han Lee; Chia-Jui Liu (Fish Physiology and Biochemistry, 2025)

P30-23 Boosting Early-Stage ADC Toxicity assessment through human in vitro cell models - B. Recolin; C. Rodger; J. Caruana Santiago; S. Randle; R. Foreman; K. Khan; M. Barbara; J. Kwon; R. Lucey; K. Pryde; M.-Y. Lee; S. Liu; et al. (Toxicology Letters, 2025)

S-vacancy-rich MoS2 for enhanced BPA degradation involved peroxymonosulfate activation: sustainable transformation of toxic V(V) into a homogeneous catalyic system - Jingjing Liu; Shanqi Liang; Ting Xiang; Lei Li; Pin Gao; Juan Zhou (Journal of Water Process Engineering, 2025)

Towards sustainable construction: A cost-effective framework for bird monitoring from on-site collected videos leveraging deep active learning and synthetic training data - Hao Xu; Jun Kang Chow; Pin Siang Tan; Xin Mao; Kuan-fu Liu; Yu-Hsing Wang (Journal of Cleaner Production, 2025)

High molecular diversity of potentially harmful heterotrophic dinophytes in tropical shrimp aquaculture ponds reveals a new dinophyte Malayana penaeicida gen. et sp. nov. (Peridiniales, Dinophyceae) - Siti Nursyuhada Baharudin; Kieng Soon Hii; Nur Fatihah Mohd Azmi; Nur Syazwani Kassim; Nursyahida Abdullah; Sing Tung Teng; Minlu Liu; Koyo Kuwata; Mitsunori Iwataki; Haifeng Gu; Po Teen Lim; Chui Pin Leaw (Harmful Algae, 2025)

Aging of textile-based microfibers in both air and water environments - Shuyu Ma; Xiaopeng Min; Lin Xu; Xiaolong Jiang; Yanan Liu; Pin Gao; Peng Ji; Hyunjung Kim; Li Cai (Water Research, 2025)

Oncolytic avian reovirus regulates the TLR3-IRF3-IFN-γ-JAK-STAT1 and TLR3-NF-κB-IFN-γ-JAK-STAT1 pathways inducing autophagy in murine melanoma cells - Chao-Yu Hsu; Zi-Yang Lo; Yi-Ying Wu; Wei-Ru Huang; Tz-Chuen Ju; Kuo-Pin Chuang; Lon-Fye Lye; Muhammad Munir; Hung-Jen Liu (Veterinary Microbiology, 2025)

In vivo molecular imaging of drug resistance in neuroblastoma using APE1 cyclically cleaved and miR-514a self-recycled programmable allosteric DNA nanomachine - Wancun Zhang; Zhenzhen Tian; Pin Zhang; Lifeng Li; Zhidan Yu; Meng Sun; Kangbo Liu; Ligong Hou; Jie Zhang; Mengxin Zhang; Xianwei Zhang (Chemical Engineering Journal, 2025)

Upregulation of circRNA_0002286 protects against brain ischemia/reperfusion injury after remote ischemic postconditioning via microRNA-124-3p/VLCAD axis - Chun-Yan Li; Wei Ma; Jin-Wei Yang; Wei Liu; Kuang-Pin Liu; Xiao-Hua Weng; Shou-Rui Niu; Shen Li; Jian-Hui Guo; Li-Yan Li (Journal of Molecular Histology, 2025)

Mitigating non-point source pollution in tea plantations: SWAT modeling and field validation of slow-release fertilizers - Chia-Chun Ho; Pin-Chih Shih; Li-Chi Chiang; Yi-Xuan Lin; Hsiu-Feng Liu; Wen-Guei Chang; Guan-Zhou Lin (Environmental Monitoring and Assessment, 2025)

Genome-wide identification, expression analysis and transcriptional regulation of major histocompatibility complex class I genes in mandarin fish Siniperca chuatsi - Jing Hou; Min Chang Li; Lu Qi; Wei Hao; Lan Hao Liu; Zhen Gan; Bei Huang; Wen Shu Huang; Li Wang; Li Li; Shan Nan Chen; Pin Nie (Aquaculture, 2025)

The mechanism of perilla oil in regulating lipid metabolism - Jiawei Xia; Yi Wang; Xin Li; Li Liu; Pin Zhang; Wendong Dai; Peng Luo; Guoze Wang; Yanhong Li (Food Chemistry, 2025)

Effect-directed analysis of the overlooked Ralstonia insidiosa induced Listeria monocytogenes aggregation under nutrient stress - Xifeng Zuo; Pin Chen; Zhe Liu; Qingyan Pan; Keying Li; Si Cheng; Ailing Guo (Food Bioscience, 2025)

Enhanced SERS performance through defect-guided growth of 2D/3D AuAg nanoplates for chemical sensing and cellular imaging applications - Kuan-Wen Liu; Pei-Yu Sie; Hsi-Ying Chen; Fong-I Ho; Po-Sheng Huang; Pin Chieh Wu; Mei-Yi Liao (Analytica Chimica Acta, 2025)

Recent progress in optimization of RANS turbulence models for accurate urban airflow and contaminant dispersion simulations - Sumei Liu; Longhui Xu; Bingqian Chen; Zhipeng Deng; Pin Li; Runmin Zhao; Qingyan Chen (Sustainable Cities and Society, 2025)

Morphology, phylogeny, and toxicity of three Gambierdiscus species from the South China Sea, including a coral-killing bloom of G. carpenteri in reef tanks - Zhaohe Luo; Xiangyuan Lin; Xiaowan Liu; Kieng Soon Hii; Haiyan Li; Yan Li; Xinya Xu; Jiaguang Xiao; Hala F. Mohamed; Xinqing Zheng; Li Zhang; Po Teen Lim; et al. (Marine Environmental Research, 2025)

Molecular characterization of TRAF gene family in snakehead (Channa argus) - Xiu Feng Han; Ming Yue Che; Xue Su; Jing Yun Tian; Lan Hao Liu; Pin Nie; Su Wang (Fish & Shellfish Immunology, 2025)

Hierarchical multi-agent deep reinforcement learning with adjustable hierarchy for home energy management systems - Leehter Yao; Pin-Yen Liu; J.C. Teo (Energy and Buildings, 2025)

Anthropogenic drought monitoring using socio-hydrological modeling for surface water deficit: Lessons from Northern Taiwan - Che-You Liu; Pin-Yi Huang; Shao-Yiu Hsu; Ching-Pin Tung; Kuo-Wei Liao (Journal of Hydrology, 2025)

Cis-regulation of the CYP6CS1 gene and its role in mediating cross-resistance in a pymetrozine-resistant strain of Nilaparvata lugens - Pin-Xuan Lin; Yu-Xuan Peng; Ji-Yang Xing; Zhao-Yu Liu; Fang-Rui Guo; Joshua A. Thia; Cong-Fen Gao; Shun-Fan Wu (Insect Biochemistry and Molecular Biology, 2025)

Temporal bloom dynamics of the marine dinoflagellate Tripos furca in the Penang Strait - Nur Fatihah Mohd Azmi; Kieng Soon Hii; Minlu Liu; Siti Nursyuhada Baharudin; Nur Syazwani Kassim; Li Keat Lee; Monaliza Mohd Din; Nurin I. Mustapa; Roziawati Mohd Razali; Haifeng Gu; Chui Pin Leaw; Po Teen Lim (Harmful Algae, 2025)

Molecular diversity of benthic harmful dinoflagellates on a tropical reef: Comparing natural and artificial substrate sampling methods using DNA metabarcoding and morphological analysis - Nur Syazwani Kassim; Li Keat Lee; Kieng Soon Hii; Nur Fatihah Mohd Azmi; Siti Nursyuhada Baharudin; Minlu Liu; Haifeng Gu; Po Teen Lim; Chui Pin Leaw (Harmful Algae, 2025)

Parafrigoribacterium soli sp. nov. and Parafrigoribacterium humi sp. nov., two novel siderophore-synthesizing species isolated from black soil - Yu-Ting OuYang; Le-Bin Chen; Jian-Yu Jiao; Zi-Xuan Hu; Jiong-Shan Wang; Tian-Hang Yang; Jun Xiao; Ting-Ting She; Pin-Jiao Jin; Shuang Wang; Lan Liu; Wen-Jun Li (Systematic and Applied Microbiology, 2025)

Life cycle assessment of CO2 capture through pressure swing adsorption using MOF-74 - Pin Wang; Zhen Pan; Zhiming Liu; Liyan Shang; Mohamad Reza Soltanian; Zhien Zhang (Gas Science and Engineering, 2025)

A “two birds one stone” strategy for self-healing marine coatings with antifouling and anticorrosion properties - Yong-Yin Cui; Tian-Cheng Chen; Jia-Ming Zhai; Ying Liu; Ye-Pin Gu; Hui-Jing Li; Yan-Chao Wu (Chemical Engineering Journal, 2025)

Therapeutic drug monitoring of methotrexate by disposable SPCE biosensor for personalized medicine - Hui Liu; Yi-Wei Liu; Ruo-Yu Yang; Mei-Juan Wu; Zi-Wei Yu; Jing-Wen Han; Chen-Zhi Zhang; Pin-Fang Huang; Ai-Lin Liu; Meng-Meng Liu (Analytica Chimica Acta, 2025)

Rich molecular diversity of ribosomal RNA genes in Pseudo-nitzschia species (Bacillariophyceae) revealed through single-strain high throughput sequencing - Hui Wang; Kuiyan Liu; Ziyan He; Yang Chen; Chui Pin Leaw; Nansheng Chen (Algal Research, 2025)

Treatment of various saline wastewaters by membrane distillation with omniphobic polyvinyl alcohol membrane - Chenshuo Wang; Lie Liu; Yuxiang Wang; Pin Hou; Jianbing Wang; Jun Wang (Desalination, 2024)

Sporelings and growth of the marine red alga, Gelidium elegans (Gelidiaceae), from Northern Taiwan - Showe-Mei Lin; Shih-Jhe Chen; Pin-Yu Huang; Li-Chia Liu; Yu-Shan Chiou (Journal of Applied Phycology, 2024)

Peteryoungia algae sp. nov. isolated from seaweeds of Gouqi Island, China, and its unique genetic features among Peteryoungia strains - Jun Yin; Min He; Xiao-Xiao Liu; Chang-Bin Ren; Hou-Hong Liu; Hai Luo; Gen Chen; Ze-Fei Wang; Sanjit Chandra Debnath; Pin-Mei Wang; Hai-Xin Chen; Dao-Qiong Zheng (Antonie van Leeuwenhoek, 2024)

Methylobacterium nigriterrae sp. nov., isolated from black soil - Le-Bin Chen; Yu-Ting OuYang; Lan Liu; Pin-Jiao Jin; Rong-Rong Huang; Wen-Yi Pan; Ying Wang; Jia-Ying Xing; Ting-Ting She; Jian-Yu Jiao; Shuang Wang; Wen-Jun Li (Antonie van Leeuwenhoek, 2024)

On-device charge engineering in 2D perovskite oxides for high performance photodetectors - Yong Zhang; Lin Wang; Xiujun Wang; Xiaohang Pan; Pin Zhao; Ye Liu; Qing Guo; Lixing Kang; Xiaosheng Fang (Chemical Engineering Journal, 2024)

New insights into biofouling worsening induced by salinity stress in membrane bioreactor: Response of quorum sensing system and its regulation role - Weilong Song; Huaning Wu; Enyu Liu; Boyan Xu; Pin Zhao; Xinhua Wang; How Yong Ng (Chemical Engineering Journal, 2024)

Nanoplastics composite norfloxacin induced changes in conformation and function of lysozyme and differential effects of co-exposure contamination - Hengyu Song; Pin Jiang; Houquan Tang; Zaifeng Wang; Xuan Ge; Xiangxiang Li; Falin He; Shuqi Guo; Guang Tian; Yuntao Qi; Shaoyang Hu; Rutao Liu (Science of The Total Environment, 2024)

Laboratorial radiative shocks with multiple parameters and first quantifying verifications to core-collapse supernovae - Lu Zhang; Jianhua Zheng; Zhenghua Yang; Tianming Song; Shuai Zhang; Tong Liu; Yunfeng Wei; Longyu Kuang; Longfei Jing; Zhiwei Lin; Liling Li; Hang Li; et al. (Science Bulletin, 2024)

Bisphenol M inhibits mouse oocyte maturation in vitro by disrupting cytoskeleton architecture and cell cycle processes - Huilei Chen; Yang Liu; Yue Huang; Pin Zhang; Danli Du; Wenhua Yu; Caiyun Wu; Hongzhen Ruan; Ping Zhou; Zhiming Ding; Huifen Xiang (Reproductive Toxicology, 2024)

Protective effects of nordalbergin against LPS-induced endotoxemia through inhibiting MAPK/NF-κB signaling pathway, NLRP3 inflammasome activation, and ROS production - Pin-Rong Chen; Chia-Yang Li; Taha Yazal; I-Chen Chen; Po-Len Liu; Yi-Ting Chen; Ching-Chih Liu; Jung Lo; Tzu-Chieh Lin; Ching-Tang Chang; Hsin-En Wu; Yuan-Ru Chen; et al. (Inflammation Research, 2024)

Ionic liquid coupled plasma promotes acetic acid production during anaerobic fermentation of waste activated sludge: Breaking the restrictions of low bioavailable substrates and altering the metabolic activities of anaerobes - Jinling He; Xinyuan Jiang; Qi Qiu; Andere Clement Miruka; Xianbao Xu; Ai Zhang; Xiang Li; Pin Gao; Yanan Liu (Water Research, 2024)

Wastewater-based epidemiology to monitor 68 NPS/conventional drug use in Taipei metropolitan area in Taiwan during and after COVID-19 pandemic - Te-Tien Ting; Pin-Chuan Chen; Ya-Chi Chang; Pin-Ju Chiang; Hsu-Cheng Li; Shih-Hsun Chen; Pei-Chieh Chen; Hai-Tien Chu; Ping-Yu Chuang; Yi-Hsin Liu; Pai-Shan Chen (Journal of Hazardous Materials, 2024)

Self-hydrogen transfer hydrogenolysis of β-O-4 bonds in lignin model compounds over NiCu/Al2O3 catalyst - Fa-Peng Wu; Le-Le Qiu; Yun-Peng Zhao; Zong-Pin Fu; Jing Liang; Jian Xiao; Jian Li; Fang-Jing Liu; Jing-Pei Cao (Fuel, 2024)

Structurally tuned polyamide membranes via the polyvinylpyrrolidone-modulated interfacial polymerization reaction for enhanced forward osmosis performance - Yao Jiang; Pin Zhao; Subo Xu; Hao Liu; Wenyan Zhang; Weilong Song; Xinhua Wang (Desalination, 2024)

Characterization and Genomic Analysis of Affinirhizobium gouqiense sp. nov. Isolated from Seawater of Gouqi Island Located in the East China Sea and Reclassification of Rhizobium lemnae to the Genus Affinirhizobium as Affinirhizobium lemnae comb. nov. - Min He; Gen Chen; Ke-Jing Li; Xing-Xing Tang; Xiao-Xiao Liu; Chang-Bin Ren; Hou-Hong Liu; Hai Luo; Sanjit Chandra Debnath; Pin-Mei Wang; Hai-Xin Chen; Dao-Qiong Zheng (Current Microbiology, 2024)

Research on the Power Output of Different Floating Wind Farms Considering the Wake Effect - Jiaping Cui; Xianyou Wu; Pin Lyu; Tong Zhao; Quankun Li; Ruixian Ma; Yingming Liu (Journal of Marine Science and Engineering, 2024)
For floating wind turbines, one of the most interesting and challenging issues is that the movement of the rotor is strongly related to its floating platform, which results in corresponding variations in the wake characteristics of the turbine. Because the aerodynamic efficiency of the downstream turbines is affected by the wake characteristics, the power output will consequently vary depending on the different types of floating wind turbines and floating wind farms used. In this study, the rotor movement, wake characteristics, and corresponding wind farm power output are analyzed using a numerical method for three typical floating wind turbines: the semisubmersible type, spar buoy type, and tension leg platform type with a 5 MW configuration. A fixed-bottom monopile wind turbine is adopted as a benchmark. The simulation results show that of the three floating wind turbines, the rotor position and wake center are most dispersed in the case of the spar buoy type, and its wake also has the lowest impact on downstream wind turbines. Additionally, the power output of the corresponding spar buoy type wind farm is also the highest at different wind speeds, followed by the semisubmersible type, tension leg platform type, and then the fixed-bottom type. In particular, at low wind speeds, the wake effects differ significantly among the various types of wind turbines.

Chromosome-Level Genome Assembly and Comparative Genomic Analysis of the Barbel Chub (Squaliobarbus curriculus) by Integration of PacBio Sequencing and Hi-C Technology - Baidong Zhang; Yanling Sun; Yang Liu; Xiaojun Song; Su Wang; Tiaoyi Xiao; Pin Nie (Fishes, 2024)
The barbel chub (Squaliobarbus curriculus), the only species in the genus, is widely distributed in freshwater lakes and rivers at different latitudes in East Asia, with fishery and biodiversity importance, and is an emerging commercially important fish in China. However, the resource of this species has dramatically declined due to anthropogenic activities such as over-exploitation, as well as water pollution. Genomic resources for S. curriculus are useful for the management and sustainable utilization of this important fish species, and also for a better understanding of its genetic variation in the region. Here, we report the chromosome-level assembly of the S. curriculus genome obtained from the integration of PacBio long sequencing and Hi-C technology. A total of 155.34 Gb high-quality PacBio sequences were generated, and the preliminary genome assembly was 894.95 Mb in size with a contig N50 being 20.34 Mb. By using Hi-C data, 99.42% of the assembled sequences were anchored to 24 pseudochromosomes, with chromosome lengths ranging from 27.22 to 58.75 Mb. A total of 25,779 protein-coding genes were predicted, 94.70% of which were functionally annotated. Moreover, S. curriculus shows resistance to grass carp haemorrhagic disease (GCHD) caused by grass carp reovirus (GCRV), which seriously hinders the status and future perspectives of commercial grass carp production. Phylogenetic analysis indicated that S. curriculus diverged with grass carp (Ctenopharyngodon idellus) approximately 20.80 million years ago. Annotations of the expanded gene families were found to be largely enriched in immune-related KEGG pathway categories. Moreover, a total of 18 Toll-like receptor (TLR) genes were identified from the whole genome of S. curriculus. The high-quality genome assembled in this study will provide a valuable resource for accelerating ecological, evolutionary, and genetic research on S. curriculus.

Nitrogen addition alleviates water loss of Moso bamboo (Phyllostachys edulis) under drought by affecting light-induced stomatal responses - Xi-pin Wu; Xiaomin Gao; Ruichang Zhang; Junwei Luan; Yi Wang; Shirong Liu (Science of The Total Environment, 2024)

Omics analysis of ‘Shine Muscat’ grape grafted on different rootstocks in response to cadmium stress - Yafeng Gu; Xiaobin Fan; Ke Jiang; Pin Liu; Huiqing Chang; Okbagaber Andom; Jieshan Cheng; Zhaojun Li (Science of The Total Environment, 2024)

Investigation of space group effects of High-Voltage spinel LiNi0.5Mn1.5O4: Unveiling the influences of fluorinate benzimidazole salt additive - Chusnul Khotimah; Rio Akbar Yuwono; Fu-Ming Wang; Chun-Chen Yang; Nae-Lih Wu; Citra Deliana Dewi Sundari; Arif Cahyo Imawan; Ching-Kai Chang; Ping-Hsuan Hsu; Pin-Cheng Huang; Guan-Yi Liu; Yi-De Tsai; et al. (Chemical Engineering Journal, 2024)

SIRT6 positively regulates antiviral response in a bony fish, the Chinese perch Siniperca chuatsi - Xiang Yang Wu; Zhi Wei Zhang; Shan Nan Chen; An Ning Pang; Xue Yun Peng; Nan Li; Lan Hao Liu; Pin Nie (Fish & Shellfish Immunology, 2024)

Climate-regulation of organic carbon export in erosive mountain settings: A case study from Taiwan since the last glacial maximum - Li-Wei Zheng; Robert G. Hilton; Yuan-Pin Chang; Rick J. Yang; Xiaodong Ding; Xufeng Zheng; Tsung-Yu Lee; Hsi-Jih Lu; Jung-Tai Lu; Yu-Shih Lin; James T. Liu; Shuh-Ji Kao (Quaternary Science Reviews, 2024)

Molecular cloning and functional analyses of C–C motif chemokine ligand 3 (CCL3) in mandarin fish Siniperca chuatsi - Xiao Liu; Jia Xiang Ji; An Ning Pang; Li Li; Pin Nie; Li Qiang Zhang; Ke Wei Zeng; Shan Nan Chen (Fish & Shellfish Immunology, 2024)

The combination of high temperature and Vibrio infection worsens summer mortality in the clam Meretrix petechialis by increasing apoptosis and oxidative stress - Jing Tian; Di Wang; Hongxia Wang; Pin Huan; Baozhong Liu (Fish & Shellfish Immunology, 2024)

MYPT1SMKO Mice Function as a Novel Spontaneous Age- and Hypertension-Dependent Animal Model of CSVD - Jian Chen; Cheng-Gang Li; Li-Xuan Yang; Yi Qian; Li-Wen Zhu; Pin-Yi Liu; Xiang Cao; Ye Wang; Min-Sheng Zhu; Yun Xu (Translational Stroke Research, 2024)

Enhanced cadmium absorption and tolerance of rice epiphytic microbes by iron oxide nanoparticles - Siduo Ding; Zhong Hu; Yuling Liu; Li Li; Yuhui Zeng; Doudou Jin; Anwei Chen; Jihai Shao; Pin Su; Si Luo (International Biodeterioration & Biodegradation, 2024)

Miocene lamprophyre and felsic volcanics in the outer zone of SW Japan: arc building through multiple sources in an active convergent margin - Pin Gao; M. Santosh; Toshiaki Tsunogae; Cheng-Xue Yang; M. Nakagawa; Sung Won Kim; Yunpeng Dong; Hai-Dong Liu (International Geology Review, 2024)

Extensive intragenomic variations of the 18S rDNA V4 region in the toxigenic diatom species Pseudo-nitzschia multistriata revealed through high-throughput sequencing - Hui Wang; Kuiyan Liu; Ziyan He; Yang Chen; Zhangxi Hu; Weizhou Chen; Chui Pin Leaw; Nansheng Chen (Marine Pollution Bulletin, 2024)

The establishment and evaluation of a swine model of deinagkistrodon acutus snakebite envenomation - Linjie Lai; Lutao Xie; Yi Chen; Wang Du; Xuelin Yang; Wanjuan Liu; Peixin Shangguan; Jiefeng Xu; Pin Lan (Toxicon, 2024)

Synergistic coupling of plasma with microbubbles for enhancing short-chain fatty acids production during sludge anaerobic fermentation: Mechanistic insights into reactive specie motivation and microbial community dynamics - Jinling He; Shuman Huang; Nan Jiang; Ai Zhang; Andere Clement Miruka; Yanan Liu; Xiang Li; Pin Gao; Gang Xue (Journal of Cleaner Production, 2024)

Enhancing trichloroethylene dechlorination capacity by utilizing granular ceramic material derived from Fe0-carbon-kaolin nanocomposite as substrate filter - Jiayan Zhu; Lishan Zhang; Junyong Liu; Shan Zhong; Zengxian Wei; Pin Gao; Jinyou Shen (Journal of Environmental Chemical Engineering, 2024)

Endowing polymeric carbon nitride photocatalyst with CO2 activation sites by anchoring atomic cobalt cluster - Yaru Shang; Yijie Hou; Xun Cao; Hengjie Liu; Xiaoli Jin; Jiawei Liu; Chunshuang Yan; Yumin Qian; Li Song; Zeming Qi; Pin Song; Yansong Zhou; et al. (Chemical Engineering Journal, 2024)

Comprehensive Multi-omics Approaches Provide Insights to Summer Mortality in the Clam Meretrix petechialis - Jing Tian; Hongxia Wang; Pin Huan; Xin Yue; Baozhong Liu (Marine Biotechnology, 2024)

Streamlining regular liquid chromatography with MALDI-TOF MS and NMR spectroscopy using automatic full-contact splitless spotting interface and flash-tap fractioning collection - Chi-Minh Truong; Yung-Cheng Jair; Hong-Po Chen; Wei-Chih Chen; Yi-Hsin Liu; Pin-Chuan Chen; Pai-Shan Chen (Analytica Chimica Acta, 2024)

The effect of lactic acid bacteria fermentation on physicochemical properties of starch from fermented proso millet flour - Tongze Zhang; Siqi Hong; Jia-Rong Zhang; Pin-He Liu; Siyi Li; Zixian Wen; Jianwei Xiao; Guirong Zhang; Olivier Habimana; Nagendra P. Shah; Zhongquan Sui; Harold Corke (Food Chemistry, 2024)

A novel baking additive: Preparation, characterization, and application of chitosan hydrochloride/carboxymethyl starch sodium nano-gel for wheat bread - Xinlai Dou; Yanling Hao; Ying Sun; Pin Yang; Linlin Liu; Yinyuan He; Yanguo Shi; Chunhua Yang; Fenglian Chen (Food Hydrocolloids, 2024)

Unleashing the contribution of nanoparticles in reforming Low-Carbon Solutions: Current Status, Trend, and prospects - Swee Pin Yeap; Kah Hou Teng; Andy Shaw; Vijay Karunamoothei; Jing Yao Sum; Ayah Tariq Abdulsalam Omer; Chengyi Liu (Chemical Engineering Journal, 2024)

Application of proteomics in identifying crucial virulence factors shared by different Streptococcus iniae isolates for developing an effective subunit vaccine against S. iniae in tilapia - Chaio-Ping Chen; Shu-Chun Chuang; Kuan-Lun Su; Li-Kai Chen; Yi-Chen Lin; Yu-Jen Wu; Shang-Pin Liu; Shao-Wen Hung; Chung-Hwan Chen; Chung-Da Yang (Aquaculture, 2024)

AaABCG20 transporter involved in cutin and wax secretion affects the initiation and development of glandular trichomes in Artemisia annua - Xueqing Fu; Han Zheng; Yuting Wang; Hang Liu; Pin Liu; Ling Li; Jingya Zhao; Xiaofen Sun; Kexuan Tang (Plant Science, 2024)

Do greenness and landscape indices for greenspace correlate with suicide ratio? - Hsiao-Yun Lee; Hao-Ting Chang; Samuel Herianto; Chi-Shin Wu; Wan-Yu Liu; Chia-Pin Yu; Wen-Chi Pan; Chih-Da Wu (Landscape and Urban Planning, 2024)

Simultaneous removal of organic micropollutants and metals from water by a multifunctional β-cyclodextrin polymer-supported-polyaniline composite - Pin Wang; Guangyu An; Peter Jarvis; Wen Liu; Shunke Ding; Ruixin Qu; Zhanghan Li; Cheng Ye; Wenhai Chu (Chemical Engineering Journal, 2024)

Reverse genetic study reveals the molecular targets of chordotonal organ TRPV channel modulators - Yu-Xuan Peng; Zhao-Yu Liu; Pin-Xuan Lin; Shao-Cong Su; Cong-Fen Gao; Shun-Fan Wu (Pesticide Biochemistry and Physiology, 2023)

Mapping harmful microalgal species by eDNA monitoring: A large-scale survey across the southwestern South China Sea - Aini Hannani Naqiah Abdul Manaff; Kieng Soon Hii; Zhaohe Luo; Minlu Liu; Ing Kuo Law; Sing Tung Teng; Mohd Fadzil Akhir; Haifeng Gu; Chui Pin Leaw; Po Teen Lim (Harmful Algae, 2023)

Polymeric PDI-based photocatalytic nanoarchitectures promoting the performance of thin film composite membrane for forward osmosis water purification - Pin Zhao; Yang Hu; Xiaoqiang An; Rong Ji; Hao Liu; Hui Zhao; Weilong Song; Yuming Dong; Xinhua Wang (Chemical Engineering Journal, 2023)

Functional evidence that FGFR regulates MAPK signaling in organizer specification in the gastropod mollusk Lottia peitaihoensis - Sujian Tan; Pin Huan; Baozhong Liu (Marine Life Science & Technology, 2023)

Metal ion assistant transformation strategy to synthesize catechol-based metal–organic frameworks from Ti3C2T precursors - Weikang Wang; Yan Bai; Pin Yang; Shuai Yuan; Feiyang Li; Weiwei Zhao; Beibei Jin; Xuan Zhang; Shujuan Liu; Daqiang Yuan; Qiang Zhao (Science Bulletin, 2023)

Performance and degradation pathway of florfenicol antibiotic by nitrogen-doped biochar supported zero-valent iron and zero-valent copper: A combined experimental and DFT study - Zheng Tang; Yifan Kong; Yan Qin; Xiaoqian Chen; Min Liu; Lu Shen; Yanming Kang; Pin Gao (Journal of Hazardous Materials, 2023)

Long-term detraining reverses the improvement of lifelong exercise on skeletal muscle ferroptosis and inflammation in aging rats: fiber-type dependence of the Keap1/Nrf2 pathway - Zhuang-Zhi Wang; Hai-Chen Xu; Huan-Xia Zhou; Chen-Kai Zhang; Bo-Ming Li; Jia-Han He; Pin-Shi Ni; Xiao-Ming Yu; Yun-Qing Liu; Fang-Hui Li (Biogerontology, 2023)

Genesis of ferromanganese nodules associated with mud volcanoes in the southeastern Dongsha waters of the northern South China Sea: Implications for regional deep Mesozoic hydrocarbon prospects - Yunfan Zhang; Pengchun Li; Yongbin Jin; Xingjian Liu; Yanlin Wang; Pin Yan; Guangjian Zhong; Yunying Zhang (Marine and Petroleum Geology, 2023)

Discrete element modelling of thermal penetration test with heating and cooling - Pin-Qiang Mo; Jing Hu; Yu-Chen Hu; Kuan-Jun Wang; Abolfazl Eslami; Liu Gao (Computers and Geotechnics, 2023)

Optimum Boron Supplementation Enhances Growth and Nutrient Uptake of Broad-Leaved Tree Seedlings - Chih-Ming Lai; Yao-Moan Huang; Chiung-Pin Liu; Tzu-Hao Su (Journal of Soil Science and Plant Nutrition, 2023)

Removal of toilet paper fibers from residential wastewater: a life cycle assessment - Xiaoyu Wang; Guoqiang Liu; Weimin Sun; Zhiguo Cao; Huaqing Liu; Yiqun Xiong; Baoqin Li; Xiaoxu Sun; Yongbin Li; Rui Xu; Duanyi Huang; Pin Gao (Environmental Science and Pollution Research, 2023)

Molecular cloning and functional analysis of polymeric immunoglobulin receptor, pIgR, gene in mandarin fish Siniperca chuatsi - Jia Xiang Ji; Lin Zhang; Li Li; Kai Lun Wang; Jing Hou; Lan Hao Liu; Bo Li; Bai Dong Zhang; Nan Li; Shan Nan Chen; Pin Nie (Fish & Shellfish Immunology, 2023)

A Novel Approach to Three-Dimensional Inference and Modeling of Magma Conduits with Exploration Data: A Case Study from the Jinchuan Ni–Cu Sulfide Deposit, NW China - Xiancheng Mao; Pin Liu; Hao Deng; Zhankun Liu; Longjiao Li; Yushan Wang; Qixing Ai; Jianxin Liu (Natural Resources Research, 2023)

Detection of live SARS-CoV-2 virus and its variants by specially designed SERS-active substrates and spectroscopic analyses - Jaya Sitjar; Jiunn-Der Liao; Han Lee; Huey-Pin Tsai; Jen-Ren Wang; Chien-Hsiung Chen; Hao Wang; Bernard Haochih Liu (Analytica Chimica Acta, 2023)

Estimating divergent forest carbon stocks and sinks via a knife set approach - Shitephen Wang; Keito Kobayashi; Satoru Takanashi; Chiung-Pin Liu; Dian-Rong Li; San-Wen Chen; Yu-Ting Cheng; Kai Moriguchi; Masako Dannoura (Journal of Environmental Management, 2023)

Effect of starch addition on the physicochemical properties, molecular interactions, structures, and in vitro digestibility of the plant-based egg analogues - Zhou Lu; Yi Liu; Yi En Jayne Lee; Andrew Chan; Pin-Rou Lee; Hongshun Yang (Food Chemistry, 2023)

Discovery of pockmarks in the Zengmu Basin, southern South China Sea and the implication - Yanlin Wang; Guanghong Tu; Junhui Yu; Pin Yan; Yongbin Jin; Changliang Chen; Jie Liu (Journal of Oceanology and Limnology, 2023)

Cytotoxic triterpenoids from the roots of Bupleurum scorzonerifolium - Dan-Qi Li; Zi-Wei Zhao; Fan Jiang; Da Liu; Xiao-Jing Wu; Xue-Gui Liu; Pin-Yi Gao (Phytochemistry Letters, 2023)

Nitrogen addition alleviates drought effects on water status and growth of Moso bamboo (Phllostachys edulis) - Xi-Pin Wu; Shirong Liu; Junwei Luan; Yi Wang; Xiaomin Gao; Chen Chen (Forest Ecology and Management, 2023)

Monitoring of tree tilt motion using lorawan-based wireless tree sensing system (IoTT) during super typhoon Mangkhut - Wai Yi Chau; Yu-Hsing Wang; Siu Wai Chiu; Pin Siang Tan; Mei Ling Leung; Hoi Lun Lui; Jimmy Wu; Yun Man Lau; Kuan-Fu Liu; Billy Chi Hang Hau (Agricultural and Forest Meteorology, 2023)

Carbon emission reduction policy with privatization in an oligopoly model - Junlong Chen; Chaoqun Sun; Yajie Wang; Jiali Liu; Pin Zhou (Environmental Science and Pollution Research, 2023)

Corrigendum to “Comparative efficacy of omega-3 polyunsaturated fatty acids on major cardiovascular events: A network meta-analysis of randomized controlled trials” [Progress in Lipid Research. 2022 Oct 28;88:101196. doi: 10.1016/j.plipres.2022.101196] - Bo Yang; Ping-Tao Tseng; Xiang Hu; Bing-Yan Zeng; Jane Pei-Chen Chang; Yang Liu; Wei-Jie Chu; Shuang-Shuang Zhang; Zhi-Liang Zhou; Chih-Sheng Chu; Cheng-Ho Chang; Yu-Kang Tu; et al. (Progress in Lipid Research, 2023)

Geomorphic development of an unvegetated shingle cay on the Ximen Reef in the southern South China Sea - Shengnan Zhou; Qi Shi; Hongqiang Yang; Lirong Wang; Xiyang Zhang; Xiaoju Liu; Fei Tan; Pin Yan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Structural and functional analysis of a potent human neutralizing antibody against enterovirus A71 - Zhe Chen; Linlin Bao; Bin Zhu; Hua Fu; Shuangli Zhu; Tianjiao Ji; Ying Xue; Chuan Liu; Xurong Wang; Fengdi Li; Qi Lv; Feifei Qi; et al. (Science China Life Sciences, 2022)

Correction to: LncRNA GATA3‑AS1 promoted invasion and migration in human endometrial carcinoma by regulating the miR‑361/ARRB2 axis - Yu‑xi Liu; Shuo Yuan; Xiao‑jing Liu; Yan‑xi Huang; Pin Qiu; Jie Gao; Gao‑pi Deng (Journal of Molecular Medicine, 2022)

Introduction of poly(acrylic acid) sodium into traditional draw solution to enhance its driving capacity in forward osmosis process - Pin Zhao; Ruiping Liu; Huijuan Liu; Jianfeng Peng; Jiuhui Qu (Environmental Science and Pollution Research, 2022)

Correction to: LncRNA GATA3‑AS1 promoted invasion and migration in human endometrial carcinoma by regulating the miR‑361/ARRB2 axis - Yu‑xi Liu; Shuo Yuan; Xiao‑jing Liu; Yan‑xi Huang; Pin Qiu; Jie Gao; Gao‑pi Deng (Journal of Molecular Medicine, 2022)

Oceanobacillus saliphilus sp. nov., Isolated from Saline−Alkali Soil in Heilongjiang Province, China - Yu-Ting OuYang; Meng-Meng Li; Ai-Ping Lv; Pin-Jiao Jin; Lan Liu; Ze-Tao Liu; Jian-Yu Jiao; Wen-Jun Li; Li-Xiang Cao; Shuang Wang (Current Microbiology, 2022)

LncRNA GATA3-AS1 promoted invasion and migration in human endometrial carcinoma by regulating the miR-361/ARRB2 axis - Yu-xi Liu; Shuo Yuan; Xiao-jing Liu; Yan-xi Huang; Pin Qiu; Jie Gao; Gao-pi Deng (Journal of Molecular Medicine, 2022)

Correction to: Exercise Rehabilitation and/or Astragaloside Attenuate Amyloid-beta Pathology by Reversing BDNF/TrkB Signaling Deficits and Mitochondrial Dysfunction - Yu-Lin Wang; Chung-Ching Chio; Shu-Chun Kuo; Chao-Hung Yeh; Jui-Ti Ma; Wen-Pin Liu; Mao-Tsun Lin; Kao-Chang Lin; Ching-Ping Chang (Molecular Neurobiology, 2022)

Exercise Rehabilitation and/or Astragaloside Attenuate Amyloid-beta Pathology by Reversing BDNF/TrkB Signaling Deficits and Mitochondrial Dysfunction - Yu-Lin Wang; Chung-Ching Chio; Shu-Chun Kuo; Chao-Hung Yeh; Jui-Ti Ma; Wen-Pin Liu; Mao-Tsun Lin; Kao-Chang Lin; Ching-Ping Chang (Molecular Neurobiology, 2022)

Alteribacter salitolerans sp. nov., isolated from a saline-alkaline soil - Shuang Wang; Lei Sun; Manik Prabhu Narsing Rao; Guo-Hong Liu; Pin-Jiao Jin; Zhou-Yan Dong; Zheng-Han Lian; Xiao-Yu Hao; Ming-Yi Zhang; Wen-Jun Li (Archives of Microbiology, 2022)

Substrate damage and recovery after giant clam shell mining at remote coral reefs in the southern South China Sea - Shengnan Zhou; Qi Shi; Hongqiang Yang; Xiyang Zhang; Xiaoju Liu; Fei Tan; Pin Yan (Journal of Geographical Sciences, 2021)

Genetic improvement for aquaculture species: A promising approach for aquaculture challenges and development - Zhen‐Yu Du; Pin Nie; Jiashou Liu (Reviews in Aquaculture, 2021)

Interaction Between Amorolfine and Voriconazole Against Fusarium species - Qin Liu; Si Jiang; Kaiping Zheng; Jiquan Song; Pin Liang (Mycopathologia, 2021)

Genome sequencing and comparative genome analysis of 6 hypervirulent Klebsiella pneumoniae strains isolated in China - Ling Du; Jiaxue Zhang; Pin Liu; Xuan Li; Kewen Su; Lingyue Yuan; Zhongshuang Zhang; Dan Peng; Yingli Li; Jingfu Qiu (Archives of Microbiology, 2021)

SAA1 regulates pro-labour mediators in term labour by activating YAP pathway - Yanmin Jiang; Li Pin; Weiqun Shi; Qian Huang; Lele Wang; Huishu Liu (Molecular and Cellular Biochemistry, 2021)

Neutrophil Extracellular Traps Serve as Key Effector Molecules in the Protection Against Phialophora verrucosa - Qin Liu; Wenjuan Yi; Si Jiang; Jiquan Song; Pin Liang (Mycopathologia, 2021)
Phialophora verrucosa ( P. verrucosa ) is a pathogen that can cause chromoblastomycosis and phaeohyphomycosis. Recent evidence suggests that neutrophils can produce neutrophil extracellular traps (NETs) that can protect against invasive pathogens. As such, we herein explored the in vitro functional importance of P. verrucosa- induced NET formation. By assessing the co-localization of neutrophil elastase and DNA, we were able to confirm the formation of classical NETs entrapping P. verrucosa specimens. Sytox Green was then used to stain these NETs following neutrophil infection with P. verrucosa in order to quantify the formation of these extracellular structures. NET formation was induced upon neutrophil exposure to both live, UV-inactivated, and dead P. verrucosa fungi. The ability of these NETs to kill fungal hyphae and conidia was demonstrated through MTT and pouring plate assays, respectively. Overall, our results confirmed that P. verrucosa was able to trigger the production of NETs, suggesting that these extracellular structures may represent an important innate immune effector mechanism controlling physiological responses to P. verrucosa infection, thereby aiding in pathogen control during the acute phases of infection.

Multimodal Image Analysis of Sexual Dimorphism in Developing Childhood Brain - Xiujun Yang; Aojie Li; Lihong Li; Tingting Li; Pin Li; Manhua Liu (Brain Topography, 2021)

Prevalence and outcomes of re-positive nucleic acid tests in discharged COVID-19 patients - Hou-wei Du; Jun-nian Chen; Xiao-bin Pan; Xiao-ling Chen; Yixian-Zhang; Shuang-fang Fang; Xiao-qing Li; Pin-cang Xia; Lei Gao; Hai-long Lin; Li-min Chen; Nan Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Advances in intervention methods and brain protection mechanisms of in situ and remote ischemic postconditioning - Chun-Yan Li; Wei Ma; Kuang-Pin Liu; Jin-Wei Yang; Xian-Bin Wang; Zhen Wu; Tong Zhang; Jia-Wei Wang; Wei Liu; Jie Liu; Yu Liang; Xing-Kui Zhang; et al. (Metabolic Brain Disease, 2021)

Histopathology, Molecular Identification and Antifungal Susceptibility Testing of Nannizziopsis arthrosporioides from a Captive Cuban Rock Iguana (Cyclura nubila) - Yen-Han Chen; Meng-Jou Chi; Pei-Lun Sun; Pin-Huan Yu; Chen-Hsuan Liu; Jose F. Cano-Lira; Wen-Ta Li (Mycopathologia, 2020)

Differential time-lag effects of ambient PM2.5 and PM2.5-bound PAHs on asthma emergency department visits - Shih-Chang Hsu; Jer-Hwa Chang; Chon-Lin Lee; Wen-Cheng Huang; Yuan-Pin Hsu; Chung-Te Liu; Shio-Shin Jean; Shau-Ku Huang; Chin-Wang Hsu (Environmental Science and Pollution Research, 2020)

Integrated control of potato late blight with a combination of the photosynthetic bacterium Rhodopseudomonas palustris strain GJ-22 and fungicides - Xin Zhang; Xiaonian Li; Yu Zhang; Yue Chen; Xinqiu Tan; Pin Su; Deyong Zhang; Yong Liu (BioControl, 2020)

A hemizygous mutation in the androgen receptor gene causes different phenotypes of androgen insensitivity syndrome in two siblings by disrupting the nuclear translocation - Chunjie Liu; Yongfen Lyu; Pin Li (Molecular Genetics and Genomics, 2020)

Calycosin Preserves BDNF/TrkB Signaling and Reduces Post-Stroke Neurological Injury after Cerebral Ischemia by Reducing Accumulation of Hypertrophic and TNF-α-Containing Microglia in Rats - Chien-Chin Hsu; Ting-Wei Kuo; Wen-Pin Liu; Ching-Ping Chang; Hung-Jung Lin (Journal of Neuroimmune Pharmacology, 2020)

High contribution of hydrocarbon transformation during the removal of polycyclic aromatic hydrocarbons from soils, humin and clay by thermal treatment at 100–200 °C - Hanzhong Jia; Jinbo Liu; Kecheng Zhu; Pin Gao; Eric Lichtfouse (Environmental Chemistry Letters, 2020)

Altered Mineral Metabolism and Disequilibrium Between Calcification Promoters and Inhibitors in Chronic Hemodialysis Patients - Chia-Liang Wang; Kuan-Pin Lin; Guoo-Shyng W. Hsu; Kai-Li Liu; Chih-Hung Guo (Biological Trace Element Research, 2020)

Study of the interactions between S. pasteurii and indigenous bacteria and the effect of these interactions on the MICP - Peng Liu; Guang-hui Shao; Rong-pin Huang (Arabian Journal of Geosciences, 2019)

LpxD gene knockout elicits protection to Litopenaeus vannamei, white shrimp, against Vibrio parahaemolyticus infection - Ching-Yi Tsai; Harvey M. Santos; Shao-Yang Hu; Cheng Yu Sang; Ciara Alyssa S. Yanuaria; Ernest Nicolo G. Lola; Lemmuel L. Tayo; Karmella Marie A. Nitura; Chun Hung Liu; Kuo Pin Chuang (Aquaculture International, 2019)

Critical review of ARGs reduction behavior in various sludge and sewage treatment processes in wastewater treatment plants - Gang Xue; Mingji Jiang; Hong Chen; Min Sun; Yunfan Liu; Xiang Li; Pin Gao (Critical Reviews in Environmental Science and Technology, 2019)

Flavobacterium sharifuzzamanii sp. nov., Isolated from the Sediments of the East China Sea - Sanjit C. Debnath; Can Chen; Shu-Xia Liu; Ya-Nan Di; Dao-Qiong Zheng; Xin-Yang Li; Xue-Wei Xu; Jin-Zhong Xu; Pin-Mei Wang (Current Microbiology, 2019)

Seismic fragility and risk assessment of high-speed railway continuous-girder bridge under track constraint effect - Shengai Cui; Chen Guo; Jiao Su; Enqi Cui; Pin Liu (Bulletin of Earthquake Engineering, 2019)

Exercise Rehabilitation Attenuates Cognitive Deficits in Rats with Traumatic Brain Injury by Stimulating the Cerebral HSP20/BDNF/TrkB Signalling Axis - Willy Chou; Yu-Fan Liu; Cheng-Hsien Lin; Mao-Tsun Lin; Chi-Chun Chen; Wen-Pin Liu; Ching-Ping Chang; Chung-Ching Chio (Molecular Neurobiology, 2018)

Cytochrome P450 2AA molecular clone, expression pattern, and different regulation by fish oil and lard oil in diets of grass carp (Ctenopharyngodon idella) - Xiao-chen Shi; Jian Sun; Ai Jin; Hong Ji; Hai-bo Yu; Yang Li; Xue-xian Li; Pin Liu; Chao Li; Ji-qin Huang (Fish Physiology and Biochemistry, 2018)

Analyzing gravity anomaly variations before the 2016 Ms 6.4 earthquake in Menyuan, Qinghai with an interpolation/cutting potential field separation technique - Jin-Zhao Liu; Tong-Qing Wang; Zhao-Hui Chen; Pin Zhang; Chuan-Dong Zhu; Shuang-Xi Zhang (Applied Geophysics, 2018)

Spatiotemporal patterns of drought at various time scales in Shandong Province of Eastern China - Depeng Zuo; Siyang Cai; Zongxue Xu; Fulin Li; Wenchao Sun; Xiaojing Yang; Guangyuan Kan; Pin Liu (Theoretical and Applied Climatology, 2018)

The Influence of Humic Substances on the Sorption of Three Organic Contaminants with Different Structure and Polarity to Clay Minerals - Lichao Zhang; Pin Xiang; Xianming Bao; Minghua Xiong; Fei Liu (Water, Air, & Soil Pollution, 2017)

Autonomous cyanobacterial harmful algal blooms monitoring using multirotor UAS - Pin Lyu; Yasir Malang; Hugh H.T. Liu; Jizhou Lai; Jianye Liu; Bin Jiang; Mingzhi Qu; Stephen Anderson; Daniel D. Lefebvre; Yuxiang Wang (International Journal of Remote Sensing, 2017)

Dietary silymarin supplementation promotes growth performance and improves lipid metabolism and health status in grass carp (Ctenopharyngodon idellus) fed diets with elevated lipid levels - Peizhen Xiao; Hong Ji; Yuantu Ye; Baotong Zhang; Yongsheng Chen; Jingjing Tian; Pin Liu; Liqiao Chen; Zhenyu Du (Fish Physiology and Biochemistry, 2017)

Beneficial Effect of Astragaloside on Alzheimer’s Disease Condition Using Cultured Primary Cortical Cells Under β-amyloid Exposure - Ching-Ping Chang; Yu-Fan Liu; Hung-Jung Lin; Chien-Chin Hsu; Bor-Chih Cheng; Wen-Pin Liu; Mao-Tsun Lin; Shu-Fen Hsu; Li-Sheng Chang; Kao-Chang Lin (Molecular Neurobiology, 2016)

Characterization and evaluation of Bacillus amyloliquefaciens strain WF02 regarding its biocontrol activities and genetic responses against bacterial wilt in two different resistant tomato cultivars - Chu-Ning Huang; Chan-Pin Lin; Feng-Chia Hsieh; Sook-Kuan Lee; Kuan-Chen Cheng; Chi-Te Liu (World Journal of Microbiology and Biotechnology, 2016)

Erratum to: The phylogenetic and recombinational analysis of beak and feather disease virus Taiwan isolates - Shr-Wei Huang; Yu-Chung Chiang; Chien-Yu Chin; Pin-Chi Tang; Pan-Chen Liu; Chi-Young Wang (Archives of Virology, 2016)

The phylogenetic and recombinational analysis of beak and feather disease virus Taiwan isolates - Shr-Wei Huang; Yu-Chung Chiang; Chien-Yu Chin; Pin-Chi Tang; Pan-Chen Liu; Chi-Young Wang (Archives of Virology, 2016)

Experimental research on seismoelectric effects in sandstone - Rong Peng; Jian-Xing Wei; Bang-Rang Di; Pin-Bo Ding; Zi-Chun Liu (Applied Geophysics, 2016)

Microwave-assisted Synthesis and antifungal activity of coumarin[8,7-e][1,3]oxazine derivatives - Ming-Zhi Zhang; Rong-Rong Zhang; Wen-Zheng Yin; Xiang Yu; Ya-Ling Zhang; Pin Liu; Yu-Cheng Gu; Wei-Hua Zhang (Molecular Diversity, 2016)

Population pharmacokinetics of vancomycin in adult Chinese patients with post-craniotomy meningitis and its application in individualised dosage regimens - Wei-wei Lin; Wei Wu; Zheng Jiao; Rong-fang Lin; Chang-zhen Jiang; Pin-fang Huang; Yi-wei Liu; Chang-lian Wang (European Journal of Clinical Pharmacology, 2016)

Degradation of p-Nitrophenol in Soil by Dielectric Barrier Discharge Plasma - Rui Li; Yanan Liu; Yu Sun; Wenjuan Zhang; Ruiwen Mu; Xiang Li; Hong Chen; Pin Gao; Gang Xue; Stephanie Ognier (Water, Air, & Soil Pollution, 2015)

Ontogenetic development of adipose tissue in grass carp (Ctenopharyngodon idellus) - Pin Liu; Hong Ji; Chao Li; Jingjing Tian; Yifei Wang; Ping Yu (Fish Physiology and Biochemistry, 2015)

The sperm proteome of the Pacific oyster Crassostrea gigas and immunolocalization of heat shock proteins - Xiaohong Huang; Baozhong Liu; Pin Huan (Invertebrate Reproduction & Development, 2015)

Regulation of adipocytes lipolysis by n-3 HUFA in grass carp (Ctenopharyngodon idellus) in vitro and in vivo - Pin Liu; Chao Li; Jiqin Huang; Hong Ji (Fish Physiology and Biochemistry, 2014)

The complete mitochondrial genome of the brown leg mite, Aleuroglyphus ovatus (Acari: Sarcoptiformes): evaluation of largest non-coding region and unique tRNAs - En-Tao Sun; Chao-Pin Li; Liu-Wang Nie; Yu-Xin Jiang (Experimental and Applied Acarology, 2014)

Spatial pattern and decadal change of agro-meteorological disasters in the main wheat production area of China during 1991–2009 - Zhao Zhang; Pin Wang; Yi Chen; Shuai Zhang; Fulu Tao; Xiaofei Liu (Journal of Geographical Sciences, 2014)

Feather Keratin Deposits as Biosorbent for the Removal of Methylene Blue from Aqueous Solution: Equilibrium, Kinetics, and Thermodynamics Studies - Pin Gao; Kanzhu Li; Zhenhong Liu; Baojiang Liu; Chunyan Ma; Gang Xue; Meihua Zhou (Water, Air, & Soil Pollution, 2014)

An EGFR gene of the Pacific oyster Crassostrea gigas functions in wound healing and promotes cell proliferation - Lingling Sun; Pin Huan; Hongxia Wang; Fengsong Liu; Baozhong Liu (Molecular Biology Reports, 2014)

Development of a loop-mediated isothermal amplification method for rapid detection of pigeon circovirus - Shinn Shyong Tsai; Yeng Ling Chang; Yen Li Huang; Hung Jen Liu; Guan Ming Ke; Chwei Jang Chiou; Yao Ching Hsieh; Tsung Chou Chang; Li Ting Cheng; Kuo Pin Chuang (Archives of Virology, 2014)

Spatial and temporal changes of agro-meteorological disasters affecting maize production in China since 1990 - Zhao Zhang; Yi Chen; Pin Wang; Shuai Zhang; Fulu Tao; Xiaofei Liu (Natural Hazards, 2014)

Influence of Cosubstrates on Iopromide Degradation by Pseudomonas sp. I-24 - Bingjie Xu; Pin Gao; Zhenhong Liu; Gang Xue; Yanan Liu; Fan Wu (Water, Air, & Soil Pollution, 2014)

The heat deficit index depicts the responses of rice yield to climate change in the northeastern three provinces of China - Zhao Zhang; Xiaofei Liu; Pin Wang; Jiabing Shuai; Yi Chen; Xiao Song; Fulu Tao (Regional Environmental Change, 2014)

MicroRNA-124 (miR-124) Regulates Ku70 Expression and is Correlated with Neuronal Death Induced by Ischemia/Reperfusion - Fei Zhu; Jing-Li Liu; Jing-Pin Li; Fang Xiao; Zhao-Xia Zhang; Lei Zhang (Journal of Molecular Neuroscience, 2014)

Improvement of a drainage system for flood management with assessment of the potential effects of climate change - Hsiang-Kuan Chang; Yih-Chi Tan; Jihn-Sung Lai; Tsung-Yi Pan; Tzu-Ming Liu; Ching-Pin Tung (Hydrological Sciences Journal, 2013)

Associations of T helper 1, 2, 17 and regulatory T lymphocytes with mortality in severe sepsis - Huang-Pin Wu; Kong Chung; Chun-Yao Lin; Bor-Yiing Jiang; Duen-Yau Chuang; Yu-Chih Liu (Inflammation Research, 2013)

Protective role of growth hormone against hyperhomocysteinemia-induced glomerular injury - Caixia Li; Min Xia; Justine M. Abais; Xiaocheng Liu; Ningjun Li; Krishna M. Boini; Pin-Lan Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Increasing concentrations of aerosols offset the benefits of climate warming on rice yields during 1980–2008 in Jiangsu Province, China - Jiabing Shuai; Zhao Zhang; Xiaofei Liu; Yi Chen; Pin Wang; Peijun Shi (Regional Environmental Change, 2013)

Fibroblast growth factor (Fgf) signaling pathway regulates liver homeostasis in zebrafish - Su-Mei Tsai; Da-Wei Liu; Wen-Pin Wang (Transgenic Research, 2013)

Cordyceps sinensis protects against renal ischemia/reperfusion injury in rats - Hua-Pin Wang; Ching-Wen Liu; Hsueh-Wen Chang; Jen-Wei Tsai; Ya-Zhu Sung; Li-Ching Chang (Molecular Biology Reports, 2013)

Impact of chilling injury and global warming on rice yield in Heilongjiang Province - Xiaofei Liu; Zhao Zhang; Jiabing Shuai; Pin Wang; Wenjiao Shi; Fulu Tao; Yi Chen (Journal of Geographical Sciences, 2013)

A new viewpoint of hazard assessment and management for Taiwan’s insurance issues - Cheng-Wu Chen; Kevin Fong-Rey Liu; Meng-Lung Lin; Chun-Pin Tseng (Natural Hazards, 2013)

Hazard management and risk design by optimal statistical analysis - Cheng-Wu Chen; Kevin Fong-Rey Liu; Chun-Pin Tseng; Wen-Ko Hsu; Wei-Ling Chiang (Natural Hazards, 2012)

Identification of Putative Artemisia annua ABCG Transporter Unigenes Related to Artemisinin Yield Following Expression Analysis in Different Plant Tissues and in Response to Methyl Jasmonate and Abscisic Acid Treatments - Ling Zhang; Xu Lu; Qian Shen; Yunfei Chen; Tao Wang; Fangyuan Zhang; Shaoyan Wu; Weimin Jiang; Pin Liu; Lida Zhang; Yueyue Wang; Kexuan Tang (Plant Molecular Biology Reporter, 2012)

RNAi assay in primary cells: a new method for gene function analysis in marine bivalve - Yanan You; Pin Huan; Baozhong Liu (Molecular Biology Reports, 2012)

The nicotine dependence phenotype, time to first cigarette, and larynx cancer risk - Joshua E. Muscat; Hsiao-Pin Liu; Craig Livelsberger; John P. Richie; Steven D. Stellman (Cancer Causes & Control, 2012)

Transcriptomic Analysis of the Clam Meretrix meretrix on Different Larval Stages - Pin Huan; Hongxia Wang; Baozhong Liu (Marine Biotechnology, 2012)

Rescue of Newcastle disease virus from cloned cDNA using an RNA polymerase II promoter - Bao-yu Li; Xue-rui Li; Xi Lan; Xiang-pin Yin; Zhi-yong Li; Bin Yang; Ji-xing Liu (Archives of Virology, 2011)

Effects of Simulated Acid Rain on the Antioxidative System in Cinnamomum philippinense Seedlings - En-U Liu; Chiung-Pin Liu (Water, Air, & Soil Pollution, 2011)

Typhoon Disturbance and Forest Dynamics: Lessons from a Northwest Pacific Subtropical Forest - Teng-Chiu Lin; Steven P. Hamburg; Kuo-Chuan Lin; Lih-Jih Wang; Chung-Te Chang; Yue-Joe Hsia; Matthew A. Vadeboncoeur; Cathy M. Mabry McMullen; Chiung-Pin Liu (Ecosystems, 2011)

Appraisal of affordable green subsidy of rice paddy in Taiwan - Chen-Wuing Liu; Shih-Wei Zhang; Hsing-Pin Yao; Kuo-Hua Lin; Wei-Taw Lin (Paddy and Water Environment, 2010)

Construction and Characterization of a Bacterial Artificial Chromosome (BAC) Library of Pacific White Shrimp, Litopenaeus vannamei - Xiaojun Zhang; Yang Zhang; Chantel Scheuring; Hong-Bin Zhang; Pin Huan; Bing Wang; Chengzhang Liu; Fuhua Li; Bin Liu; Jianhai Xiang (Marine Biotechnology, 2010)

An approach to analyzing taxonomic patterns of protozoan communities for monitoring water quality in Songhua River, northeast China - Xiaoli Tan; Xinlu Shi; Guijie Liu; Henglong Xu; Pin Nie (Hydrobiologia, 2010)

Isolation and characterization of 30 novel polymorphic microsatellite loci from Japanese halfbeak, Hyporhamphus sajori (Temminck et Schlegel, 1846) - Shi-Chao Xing; Gen-Bo Xu; Guan-Pin Yang; Shan-Shan Liu; Xiao-Lin Liao; Yong-sheng Tian; Song-Lin Chen (Conservation Genetics, 2009)

Dual-rhodamine urea derivative, a novel chemidosimeter for Hg(II) and its application in imaging Hg(II) in living cells - Pin-xian Xi; Liang Huang; Heng Liu; Peng-fei Jia; Feng-juan Chen; Min Xu; Zheng-zhi Zeng (JBIC Journal of Biological Inorganic Chemistry, 2009)

Serial cytokine levels in patients with severe sepsis - Huang-Pin Wu; Chian-Kuang Chen; Kong Chung; Jo-Chi Tseng; Chung-Ching Hua; Yu-Chih Liu; Duen-Yau Chuang; Chung-Han Yang (Inflammation Research, 2009)

Effects of cyanobacterial toxin microcystin-LR on the transcription levels of immune-related genes in grass carp Ctenopharyngodon idella - Lili Wei; Baojian Sun; MingXian Chang; Yi Liu; Pin Nie (Environmental Biology of Fishes, 2009)

Recombinant ORF66 and ORFK12 antigens for the detection of human herpesvirus 8 antibodies in HIV-positive and -negative patients - Tsuey-Ching Yang; Chun-Pin Chang; Yu-Ching Lan; Chao-Li Liu; Mu-Chin Shih; Fang-Yang Wu; Cheng-Wen Lin (Biotechnology Letters, 2009)

Synthesis, Characterization, Antioxidant Activity and DNA-Binding Studies of Three Rare Earth (III) Complexes with 1-(4-Aminoantipyrine)-3-tosylurea Ligand - Pin-xian Xi; Zhi-hong Xu; Xiao-hui Liu; Feng-juan Chen; Zheng-zhi Zeng; Xiao-wen Zhang; Ying Liu (Journal of Fluorescence, 2009)

Diurnal temperature range and emergency room admissions for chronic obstructive pulmonary disease in Taiwan - Wen-Miin Liang; Wen-Pin Liu; Hsien-Wen Kuo (International Journal of Biometeorology, 2009)

Co-circulating genetically divergent A2 human metapneumovirus strains among children in southern Taiwan - Hsuan-Chen Wang; Sheng-Wen Huang; Shainn-Wei Wang; Huey-Pin Tsai; David Kiang; Shih-Min Wang; Ching-Chuan Liu; Ih-Jen Su; Jen-Ren Wang (Archives of Virology, 2008)

Ambient temperature and emergency room admissions for acute coronary syndrome in Taiwan - Wen-Miin Liang; Wen-Pin Liu; Sze-Yuan Chou; Hsien-Wen Kuo (International Journal of Biometeorology, 2008)

Detection and identification of the phytoplasma associated with pear decline in Taiwan - Hsiu-Lin Liu; Ching-Chung Chen; Chan-Pin Lin (European Journal of Plant Pathology, 2007)

Effects of the 921 earthquake on the water quality in the upper stream at the Guandaushi experimental forest - Chiung Pin Liu; Bor Han Sheu (Water, Air, & Soil Pollution, 2007)

Assessing Genetic Diversity of Chinese Cultivated Barley by STS Markers - Xiwen Chen; Shaoying Guo; Defu Chen; Pin Liu; Xiangdong Jia; Lijun Sun (Genetic Resources and Crop Evolution, 2006)

Water Chemistry and Temporal Variation of Nutrients in Stemflow of Three Dominant Tree Species in the Subtropics of the Fu-Shan Forest - Chiung-Pin Liu; Hen-Biau King; Ming-Kuang Wang; Yue-Joe Hsia; Jeen-Lian Hwong (Water, Air, & Soil Pollution, 2004)

The Activation Mechanism of Class-III G-Protein Coupled Receptors - J.-P. Pin; J. Kniazeff; C. Goudet; A.-S. Bessis; P. Rondard; J. Liu; F. Acher; T. Galvez; L. Przeau (Medicinal Chemistry Research, 2004)